2020
DOI: 10.1088/1751-8121/ab9462
|View full text |Cite
|
Sign up to set email alerts
|

A note on the Drinfeld associator for genus-zero superstring amplitudes in twisted de Rham theory

Abstract: The string corrections of tree-level open-string amplitudes can be described by Selberg integrals satisfying a Knizhnik–Zamolodchikov (KZ) equation. This allows for a recursion of the α′-expansion of tree-level string corrections in the number of external states using the Drinfeld associator. While the feasibility of this recursion is well-known, we provide a mathematical description in terms of twisted de Rham theory and intersection numbers of twisted forms. In particular, this leads to purely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…As an example, let us state the first couple of orders of the series expansion of a typical integral Z tree n : The analogous expressions for arbitrary orders in the α -expansion of n-point disk integrals can for instance be generated from the Drinfeld associator [12,45] or Berends-Giele recursions [15]. 3 The Berends-Giele method in ref.…”
Section: Tree Level: Genus Zeromentioning
confidence: 99%
See 3 more Smart Citations
“…As an example, let us state the first couple of orders of the series expansion of a typical integral Z tree n : The analogous expressions for arbitrary orders in the α -expansion of n-point disk integrals can for instance be generated from the Drinfeld associator [12,45] or Berends-Giele recursions [15]. 3 The Berends-Giele method in ref.…”
Section: Tree Level: Genus Zeromentioning
confidence: 99%
“…, b n ) whose decomposition in the (n−3)! bases expanded in [12,45] can be generated from the techniques in ref. [52].…”
Section: Tree Level: Genus Zeromentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was observed that using recursion relations for computing intersection numbers can be further refined by relating them to dlog forms at each step of the recursive algorithm [20]. Other recent intersection-theory approaches include [21][22][23].…”
Section: Introductionmentioning
confidence: 99%